Plan de negocio para la implantación de una microempresa de elaboración y comercialización de ropa deportiva en el cantón La Maná provincia de Cotopaxi, año 2012 - Contreras Salvatierra, Olga Magdalena (2015)
The project aims to create a business plan for the establishment of a small business for development and commercialization of sportswear in La Maná canton Cotopaxi Province in 2012, in the absence of a suitable location that covers the needs of the citizens, this brings that people travel to other places to buy clothing in search of quality and new designs, the type of research that was used to develop the same was: exploratory, descriptive and correlational research. By applying the technique surveys achievement data known as: demand, supply, tastes and preferences of customers, the economic study throw an IRR of TIR 20,79%, VAN and a NPV of 62.740,50; and a benefit cost ratio of 3,82 and concluded that the project is feasible for implementation.